The Impact of Servicescape Perception on Perceived E-Commerce Value and Client Loyalty - Jeffri Prayitno Bangkit Saputra (International Journal of Informatics and Information Systems, 2021)
While previous research on e-servicescapes has focused on the ordinary Internet user, several studies show that heavy Internet users are the target audience. To maximize firm profitability, it is vital to understand the nature of heavy user consumption; hence, this study examines the primary components of e-servicescapes and their relationship to buy intent using moderated data from heavy and light Internet users. Three hundred and forty-two genuine internet users with online purchasing experience answered an online questionnaire, and discrepancies were determined using structural equation modeling. For ordinary users, aesthetic appeal and interaction are significant factors in purchase intention; for heavy users, interactivity is the most important attribute, followed by aesthetic appeal, layout, and functionality; and for light users, aesthetic appeal is the sole consideration. Additionally, our data show that financial stability does not help heavy, regular, or light users. We demonstrate how heavy and light Internet users evaluate e-servicescapes to signal quality attributes and contribute to their cognitive responses and purchase intentions based on their consumption traits by integrating purchase intentions with e-service quality and segmentation theory in e-servicescapes. It is advised that online merchants identify heavy and light users, rethink their current e-servicescapes, and apply more tailored marketing methods to attract and retain heavy and light users, as well as increase their purchase intent. While this study concentrated on the most salient characteristics of heavy users, more research is required to explicate additional critical mediators. This poll makes no mention of the three kinds of websites or product qualities. Finally, demographic and psychological variables such as gender and personal characteristics may act as significant mediators in the link between the e-servicescape and purchase intention, but their relevance requires more research.